Efeitos da mudança climática na distribuição potencial e áreas que protegem dois marsupiais neotropicais associados a ambientes aquáticos - Ribeiro-Souza, Paula Danyelle (2020)
The contraction of suitable habitat due to the effects of climate change can result in a species becoming susceptible to extinction. Faced with this, protect areas are fundamental for conservation and management of biodiversity in the scenario of climate change. We address these issues using the ensemble technique to generate potential distribution models for Chironectes minimus and Lutreolina crassicaudata, accounting for the effects of climate change for the present-day and the future scenarios (2050). We selected these target species because their occurrence covers habitats of great relevance for biodiversity conservation, such as river ecosystems. Therefore, the protection of C. minimus and L. crassicaudata by Strictly Protected Areas (SPAs) was evaluated in both present-day and future scenarios. In light of our models, we recommend priority areas for the conservation of both species for our future scenario, emphasizing the establishment of conservation efforts across national boundaries. The results of this study suggest that both species will suffer a significant restriction of their potential distributions by 2050, resulting in the likelihood of their becoming threatened or extinct in some countries. Our models predict that the loss of suitable areas will be greater for C. minimus, leaving only 41% stable area. Our models suggest that the current system of SPAs in the Neotropical region, with relation to the stable areas of climatic suitability, is insufficient to protect L. crassicaudata, with only 3.4% of its potential distribution area present-day and 3.97% in the future within their boundaries. Our predicted distributional responses of these two marsupials to climate change suggest strong impacts on the overall protection of biodiversity in aquatic environments in the Neotropical region. We highly recommend the prioritized planning implementation of transboundary SPAs in stable areas of species distribution in order to maintain the appropriate climatic conditions for the persistence of these marsupials and the ecosystems with which they are associated.